Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1099/mgen.0.000201
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of the commercially important pathogen Renibacterium salmoninarum within the Chilean salmon industry

Abstract: Renibacterium salmoninarum is the causative agent of bacterial kidney disease (BKD), which is a commercially important disease of farmed salmonids. Typing by conventional methods provides limited information on the evolution and spread of this pathogen, as there is a low level of standing variation within the R. salmoninarum population. Here, we apply whole-genome sequencing to 42 R. salmoninarum isolates from Chile, primarily from salmon farms, in order to understand the epidemiology of BKD in this country. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 23 publications
(33 reference statements)
1
23
0
1
Order By: Relevance
“…For instance, rainbow trout and Atlantic salmon are comparatively resistant to BKD [8,9] while two subfamilies of Salmonidae: Thymallinae, and Coregoninae are considered to be particularly sensitive [10]. BKD is a chronic, slow developing infection and has a significant impact on fish populations, both wild and farmed [11]. Mortality occurs mostly in 6 to 12 month-old juvenile salmon and pre-spawning adults [12].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, rainbow trout and Atlantic salmon are comparatively resistant to BKD [8,9] while two subfamilies of Salmonidae: Thymallinae, and Coregoninae are considered to be particularly sensitive [10]. BKD is a chronic, slow developing infection and has a significant impact on fish populations, both wild and farmed [11]. Mortality occurs mostly in 6 to 12 month-old juvenile salmon and pre-spawning adults [12].…”
Section: Introductionmentioning
confidence: 99%
“…These authors were able to identify four groups corresponding to the multiple introductions of this bacterium from different countries over the course of the years. This study demonstrated the importance of fish transfer in the international spread of the bacterium [ 1 ].…”
Section: Historical Background and Classificationmentioning
confidence: 87%
“…Similarly, Bayliss et al [ 1 ] applied whole genome sequencing (WGS) to construct a phylogenetic tree for 42 R. salmoninarum isolates identified in Chile between 2012 and 2016. These authors were able to identify four groups corresponding to the multiple introductions of this bacterium from different countries over the course of the years.…”
Section: Historical Background and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, using less water surface, Chile competes to Norway in salmon production [12]. As consequence, Chilean aquaculture has faced several sanitary problems, related with outbreaks of viruses such as infectious pancreatic necrosis virus (IPNV) [13] and infectious salmon anemia virus (ISAV) [14]; bacterial pathogens such as Piscirickettsia salmonis [15], Flavobacterium psychrophilum [16], and Renibacterium salmoninarum [17]; and parasites such as Caligus rogercresseyi [15]. Diseases caused by viruses are one of the great challenges of Chilean salmon farming industry; the first virus being identified in Chile was IPNV, which is highly persistent and causes severe mortality.…”
Section: Microbiological Threats Facing Chilean Aquaculturementioning
confidence: 99%